AB0193 Semaphorin4a induces th17 cytokine production in systemic sclerosis. (12th June 2018) - García Pérez, S.; Carvalheiro, T.; Affandi, A.J.; Malvar Fernandez, B.; Dullemond, I.; Cossu, M.; Marut, W.; Reedquist, K.A.; Radstake, T.R.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterised by inflammation, vascular injury and excessive fibrosis in different organs. Different studies have shown that Th17 cells and Th17 cytokines (IL-17, IL-21 and IL-22) play a key role in the pathogenesis of the disease. Semaphorin 4A (Sema4A) is a transmembrane protein that belongs to a large family of proteins initially described as ligands essential for neuronal development. Further studies have shown that they also play a role in other biological processes including the control of immune responses. Importantly, Sema4A has a critical role in the skewing of CD4 + T cells towards a Th17 phenotype. However, it is unknown if Sema4A contributes to the elevated number of Th17 cells observed in SSc patients. Objectives: The aim of this study was to analyse the potential role of Sema4A as a regulator of Th17-skewing in SSc. Methods: Plasma levels of Sema4A were measured by ELISA. Expression of Sema4A and its receptors PlexinB2, PlexinD1 and neuropilin-1 (NRP-1) was determined by (q)uantitative PCR, western blot and flow cytometry in monocytes and CD4 + T cells of healthy donors (HD) and SSc patients. Monocytes were stimulated with Poly IC (5 µg/ml) or CXCL-4 (5 µg/ml) and Sema4A expression was analysed by qPCR and ELISA. CD4 + T cells were stimulated with anti-CD3/anti-CD28 beads (ratio 1 bead: 5 cells) alone or in combination with recombinant human Sema4A (200 ng/ml), in the presence or absence of neutralising anti-NRP1 or PlexinD1 antibodies, and the expression of PlexinB2, PlexinD1, NRP-1 and the production of Th17 cytokines was analysed by qPCR, ELISA and flow cytometry. Results: Plasma levels of Sema4A were significantly higher in SSc patients compared to healthy controls (HC) and positively correlated (r=0.611) with the skin disease severity. Sema4A and PlexinB2 expression was significantly higher in monocytes and CD4 + T cells from SSc patients, respectively. Moreover, Poly IC and CXCL-4 significantly up-regulated the expression and secretion of Sema4A in monocytes from SSc patients, and CD4 + T cells stimulation with anti-CD3/anti-CD28 beads increased the expression of PlexinB2 and NRP-1 in both HC and SSc patients. Finally, functional assays showed that Sema4A significantly enhanced the expression of Th17 cytokines induced by CD3/CD28 in CD4 + T cells from both HC and SSc patients, and the blocking of the Sema4A signalling using neutralising antibodies anti-PlexinD1 and anti-NRP-1 significantly reduced this expression. Importantly, the Sema4A-induced IL-17 secretion was significantly higher in stimulated CD4 + T cells from SSc patient compared to HC. Conclusions: Sema4A signalling is deregulated in SSc patients and plays an important role in Th17 skewing. Therefore, Sema4A and its receptors could be promising therapeutic targets for the treatment of SSc. Disclosure of Interest: None declared